Students’ Creativity in Suspension Bridge Miniature Projects Based on Field-Dependent Cognitive Style - Nova Febrian Alfianita; Yurizka Melia Sari (MATHEdunesa, 2026)
Creativity is the ability to generate new ideas that are needed in the world of work, which demands innovation and solutions to complex problems. In the context of education, students still find it difficult to develop their creativity because learning is still carried out in a conventional manner. This research is a qualitative study that aims to describe the creativity of high school students in designing miniature suspension bridges using a STEM approach to quadratic functions, as viewed from a field-dependent cognitive style. The data for this study was collected from twenty-eight high school students at a school in Malang City. The research data was collected through the group embedded figures test, mathematics ability test, miniature suspension bridge products, and interviews. The research subjects were two students with a field-dependent cognitive style. The results of the study indicate that cognitive style influences how students model quadratic functions in a miniature suspension bridge project, and that students with a field-dependent cognitive style do not utilize quadratic functions when constructing the suspension arches. Therefore, further research is recommended to strengthen the integration of mathematical concepts in STEM projects.